1974
DOI: 10.1002/cpt1974163part1455
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of intravenous infusion of L‐tryptophan in normal subjects

Abstract: The effects of intravenous infusion of L‐tryptophan at doses of 75 and 100 mg/kg were compared with that of normal saline in healthy volunteers by means of a series of psychological and physiological measures. The 100 mg/kg infusion produced a 40 fold increase in free tryptophan and an 8 fold increase in the bound form. Few of the objective tests showed any differences. The electroencephalogram showed a significant increase in slow‐wave activity (4.0 to 7.5 Hz) and a trend toward decreased fast‐wave activity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…A similar increase oc curring in a placebo-treated group has been described by Greenwood et al [5] and illustrated in the findings of Spinweber et al [7], whereas such an increase was not found in the group receiving L-tryptophan. This might be interpreted as indicating that L-tryptophan dimin ishes the increase in beta activity that normally might occur, possibly because of circadian rhythms.…”
Section: Tryptophansupporting
confidence: 81%
See 2 more Smart Citations
“…A similar increase oc curring in a placebo-treated group has been described by Greenwood et al [5] and illustrated in the findings of Spinweber et al [7], whereas such an increase was not found in the group receiving L-tryptophan. This might be interpreted as indicating that L-tryptophan dimin ishes the increase in beta activity that normally might occur, possibly because of circadian rhythms.…”
Section: Tryptophansupporting
confidence: 81%
“…Spinweber et al [7] found a 4-gram dose of L-tryptophan to increase the intensity of the theta waves, whereas Oswald et al [4] failed to find any clear effect on the EEG with 5 g of L-tryptophan. In a study by Greenwood et al [6] the same amount caused increased activity in the slow wavebands of the EEG (theta and delta), as was also the case after an intrave nous infusion of L-tryptophan (75-100 mg/kg) [5], Even though a marked decrease in the activity of the alpha frequency band following L-tryptophan adminis tration was recorded in all EEG leads, this decrement was found significant only in the occipital and right tem poral regions. In contrast the alpha amplitude increased in the placebo group, though not significantly.…”
Section: Tryptophanmentioning
confidence: 74%
See 1 more Smart Citation
“…In an earlier attempt to clarify these conflicting results (Greenwood, Friedel, Bond, Curzon & Lader, 1974) we gave tryptophan by infusion. The effects were assessed on a series of psychological and physiological measures known to be sensitive to psychotropic drug effects (Bond & Lader, 1972;Sakalis, Curry, Mould & Lader, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Bloxam and Curzon (1978) reported that brain Trp concentration was more influenced by changes in plasma free Trp concentration than by changes in plasma concentration of competing amino acids. While Smith and Prockop (1962) observed various neuropsychiatric signs and symptoms following oral administration of Trp (30-90 mg/kg), Greenwood et al (1974) were unable to detect any overt mood change by intravenous infusion of Trp (75-100 mg/kg). These observations suggest that the effects of Trp on the brain function vary with the route of administration.…”
Section: Discussionmentioning
confidence: 96%